Assessing Microplastic Contamination in Shellfish: Insights from Pantai Remis Kuala Selangor, Strait of Malacca, Malaysia - Abdul Aziz, Aliyah; Osman, Mohamed Syazwan; Wan Rasdi, Nadiah; Shafie, Farah Ayuni; Feisal, Nur Azalina Suzianti; Zaki, Muhamaad Afiq; Mohd Yatim, Siti Rohana (JURNAL KESEHATAN LINGKUNGAN, 2024)
Introduction: Microplastic (MP) contamination poses a global environmental threat, affecting terrestrial and marine ecosystems, and human health. This study investigates the presence, density, and composition of MPs in three commercially important shellfish species, oriental angel wing clam (Pholas orientalis), bamboo clam (Ensis leei), and blood cockles (Tegillarca granosa) at Pantai Remis Jeram, Kuala Selangor. Methods: Microplastics in shellfish were quantitatively analyzed for their abundance, colour, size, shape, and composition using microscopic techniques and micro-Fourier Transform Infrared (FTIR). Standard experimental protocols were followed. Statistical analysis of the data was performed using SPSS to identify correlations between these parameters. Results and Discussion: Our findings reveal a significant presence of MP particles in shellfish with T. granosa exhibiting the highest density (2.417 particles/cm³) compared to E. leei (0.721 particles/cm³) and P. orientalis (1.449 particles/cm³). Fibers and fragments were the dominant MP morphotypes, primarily in black color. P. orientalis and T. granosa contained a majority of MPs within the 1 - 5 mm size range, totalling 41 and 56 particles, respectively. Shellfish samples contain polymers of cellulase acetate and polyethylene terephthalate, indicating possible origins from plastic bottles and textile fibres. A statistically significant difference in the mean MP densities in the different species of shellfish was found by one-way ANOVA analysis (p = 0.042, p < 0.05). Conclusion: This study provides relevant data on MP pollution in commercially significant shellfish species. To effectively mitigate this environmental concern and comprehend the long-term ecological ramifications of MP intake by shellfish, more research is required.